2020
DOI: 10.1177/1479973120961846
|View full text |Cite
|
Sign up to set email alerts
|

Short-Physical Performance Battery (SPPB) score is associated with postoperative pulmonary complications in elderly patients undergoing lung resection surgery: A prospective multicenter cohort study

Abstract: Elderly patients awaiting lung resection surgery often have poor physical function, which puts them at a high risk of postoperative pulmonary complications. The aim of this study was to investigate the impact of preoperative physical performance on postoperative pulmonary complications in patients awaiting lung resection surgery. In this prospective multicenter cohort study, the characteristics of patients and postoperative pulmonary complications were compared between subjects with low (<10) and high (≥10)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 29 publications
0
14
0
1
Order By: Relevance
“…For instance, recent longitudinal studies also found that the increase in one SPPB unit decreased the probability of falls by 15% and of recurrent falls by 17% over a two-year period. Of note, SPPB domains have not only been associated with falls [37][38][39] but also with sarcopenia [40], frailty [41], dyspnoea [42], postoperative complications [43], cardiovascular diseases [44], increased risk of mortality in chronic obstructive pulmonary disease (COPD) [45]., institutionalization, hospitalization and death [25,[46][47][48]. It is also noteworthy that SPPB has been used as tool for predicting disability and physical functional impairment in discharged patients with severe COVID-19 [49].…”
Section: Analysis Of Physical Performance Using the Sppbmentioning
confidence: 99%
“…For instance, recent longitudinal studies also found that the increase in one SPPB unit decreased the probability of falls by 15% and of recurrent falls by 17% over a two-year period. Of note, SPPB domains have not only been associated with falls [37][38][39] but also with sarcopenia [40], frailty [41], dyspnoea [42], postoperative complications [43], cardiovascular diseases [44], increased risk of mortality in chronic obstructive pulmonary disease (COPD) [45]., institutionalization, hospitalization and death [25,[46][47][48]. It is also noteworthy that SPPB has been used as tool for predicting disability and physical functional impairment in discharged patients with severe COVID-19 [49].…”
Section: Analysis Of Physical Performance Using the Sppbmentioning
confidence: 99%
“…A combination of physical instruments measuring different elements (for instance, aerobic fitness and muscle strength) might provide a more comprehensive view on the patient's physical condition than a single preoperative test. For example, the SPPB consists of three elements assessing muscle function (balance, walking speed and lower extremity strength) and has been shown to predict complications and mortality in lung and cardiac surgery patients [42,43]. It should also be mentioned that, although not in the scope of this review, malnutrition is also a determinant of physical frailty and contributes to sarcopenia [44] and measuring nutritional status next to other objective physical parameters may improve risk prediction.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 The SPPB has been studied across a wide range of populations; however, it is not typically included in the evaluation of physical performance following TKA. [15][16][17][18][19] As a postoperative functional outcome measurement, the SPPB has mainly been investigated and used in patients undergoing cardiac or pulmonary surgery. A low SPPB score has been associated with adverse surgical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“… 18 A SPPB score below 10 was associated with higher postoperative pulmonary complications in elderly patients undergoing lung resection. 19 Przkora et al demonstrated the utility of the SPPB in ambulatory patients undergoing pain procedures for degenerative spine disease. 20 Our findings suggest that the collection of the SPPB in the perioperative setting in patients following lower extremity joint replacement surgery is feasible and acceptable.…”
Section: Discussionmentioning
confidence: 99%